Development strategies for sustainable smallholder coffee plantations in Wagir District, Malang Regency - Parmawati, Rita; Wardana, Fitri Candra; Hardiansyah, Rizha; Rahmawati, Nadhea Oktaviantina; Gunawan, Fahdynia Karnira; Ashari, Fadhil Muhamad (Fakultas Pertanian Universitas Yudharta Pasuruan, 2024)
Introduction: The coffee plantation subsector is one of the most significant subsectors in Wagir District, Malang Regency. Sustainable practices are critical to the success of smallholder coffee crops. This research aims to create a sustainable plan for smallholder coffee crops in Wagir District, Malang Regency. Methods: Twenty farmers and five experts chosen by purposive sampling participated in the study, which was carried out in the Wagir District of Malang Regency. A questionnaire was utilized to interview participants to capture the phenomenon. Data analysis employs a hybrid approach that combines SWOT and AHP. Results: Six strategic priorities are identified by the study findings following the identification of internal and external factors in the SWOT and AHP analyses. Limitations - Second Opportunity (WO2) The most important strategy to be put into practice based on the situation on smallholder coffee plantations in Wagir District is the one with a score of 1.135. Conclusion: To have a more widespread and long-lasting impact, the primary tactic to increase the sustainability of smallholder coffee plantations in Wagir District, Malang Regency, is to work with multi-stakeholders like the local government, academic institutions, and research centers to directly educate the community or serve as resource persons in capacity building for agricultural extension workers.